Survival Rate Evaluation of Different Filler Medium of Waterless Live Fish Transportation of African Catfish (Clarias sp.) Broodstock - Ayuningtyas Ayuningtyas; Baruna Kusuma; Abdul Rahem Faqih; Yunita Maimunah (Journal of Aquaculture Development and Environment, 2018)
The supplying of live fish broodstock is routinely delivered by water. However, the traditional transportation of live fish with water results in small volume of transportation. Therefore, waterless transportation with different filler medium of waterless live fish transport is considered an alternative strategy. This research aimed to evaluate the effect of different filler medium of waterless live fish transportation on survival rate of African catfish (Clarias sp.) broodstocks. Brooders with mean weight 116 ±10,25 g were packed at 5 fish/bag for simulated 15h transportation. The bags, each 40x25x15 cm3, were filled with different treatment of medium; Sponge, newspaper, cloth, and sawdust at 3 cm thickness of sponge medium and ½ kg for newspaper, cloth and sawdust medium per bag. One bag without medium was designed as a control. Mortality, temperature, Humidity and weight gain loss were monitored throughout the experiment. After simulation, mortality, pH, DO and temperature were monitored in fiber pond over 14 days. Effect of different treatment of medium was significantly different (p < 0.05) with highest survival (100%) at sponge and cloth medium, and lowest survival (24 %) at sawdust medium. Humidity of newspaper medium and weight gain loss of sawdust medium significantly decreased and no significantly different in temperature parameter after simulated 15h transportation. It was concluded that sponge and cloth medium might be applied as a filler medium for waterless live fish transportation.